(untitled) (Research, Society and Development, 2022)
Studies prove that using aromatherapy with lavender oil generates reduction of anxiety, sedative, antidepressant, soothing, antispasmodic, analgesic and healing effects. A fact that occurs due to the inhibitory action of lavender on the hypothalamic-hypophysis-adrenal axis, which results in the reduction in the release of cortisol, the stress hormone. Promoting, on the other hand, the release of serotonin, generating a feeling of pleasure and well-being. Thus, the present study aimed, through an integrative literature review, to describe the effects of the use of lavender oil in the treatment of anxiety. The psychological effects of inhaling lavender oil occur through conscious perception, belief and expectation. Meanwhile, the pharmacological effects occur through the modulation of the cyclic activity of adenosine monophosphate (reduction of cyclic adenosine monophosphate results with sedation) and inhibition of glutamate binding (sedative effects). Thus, the use of oil is considered safe, except for rare allergic reactions, and can be beneficial in patients with anxiety and reduce the use of antipsychotic drugs.